Bilateral renal involvement in diffuse large B-cell lymphoma on fluorodeoxyglucose positron emission tomography/computed tomography - Yassir Benameur; Adnane Hammani; Kamal Doghmi; Abderrahim Doudouh (World Journal of Nuclear Medicine)
Secondary renal involvement in patients with diffuse large B-cell lymphoma (DLBCL) is rare and associated with poor prognosis. We, hereby, described a case of a patient diagnosed with DLBCL, in whom bilateral renal involvement was detected on 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT). The patient received 4 courses of chemotherapy, and follow-up 18F-FDG PET/CT revealed the complete resolution of the diffuse increased renal 18F-FDG uptake. Renal lymphoma is uncommon and 18F-FDG PET/CT is particularly useful for detecting extranodal involvement in DLBLC.